1994
DOI: 10.1111/j.1574-6976.1994.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of the extremely halophilic archaea

Abstract: The extremely halophilic archaea (family Halobacteriaceae) are the dominant heterotrophic organisms in hypersaline environments in which salt concentrations exceed 250–300 g l−1. During the last decades our knowledge on the taxonomy, physiology and biochemistry of the Halobacterium group has greatly increased. However, our understanding of the ecology of the halophilic archaea lags far behind the progess made in the study of other aspects of their biology. A few hypersaline environments, such as the Dead Sea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(70 citation statements)
references
References 105 publications
3
59
0
3
Order By: Relevance
“…Halobacteria is a typical halophilic archaeon with specifically adaptive capacity for hyperhaline environments (34). Phylogenetic Halobacterium is a type of Halobacteria that has been extensively investigated for its ability to live in saline environments and its roles in saline wastewater treatment processes (31,35). A significant community shift and the proportion decreasing of Halobacterium at 40 g/liter of NaCl in the BC indicated that the BC was severely impacted by salt damage, which is consistent with a VSS/TSS decrease in the BC.…”
supporting
confidence: 49%
“…Halobacteria is a typical halophilic archaeon with specifically adaptive capacity for hyperhaline environments (34). Phylogenetic Halobacterium is a type of Halobacteria that has been extensively investigated for its ability to live in saline environments and its roles in saline wastewater treatment processes (31,35). A significant community shift and the proportion decreasing of Halobacterium at 40 g/liter of NaCl in the BC indicated that the BC was severely impacted by salt damage, which is consistent with a VSS/TSS decrease in the BC.…”
supporting
confidence: 49%
“…Many neutral hypersaline environments at saturation point, harbour climax populations of halobacteria usually belonging to the genera Halobacterium, Haloarcula and Halorubrum [46].…”
Section: Introductionmentioning
confidence: 99%
“…Two main groups are to be found: the moderately halophilic bacteria are more abundant at intermediate salinities (1.5 -2.5 M), whereas the halophilic archaea (the halobacteria) dominate at salinities greater than 2.5 M, often imparting spectacular red pigmentation to the environment due to high levels of carotenoids [29]. Representatives of the majority of archaeal genera are characteristic of neutral saline environments (Halobacterium, Halorubrum, Haloarcula, Haloferax, Halococcus, Halobaculum, and Natrialba spp) [29,35,36,39,43,47] whereas alkaline saline environments harbour haloalkaliphilic halobacteria such as Natronomonas and Natronobacterium spp [36].The application of molecular and biochemical techniques has indicated that specific successions of halobacteria occur in hypersaline waters as the waters become concentrated.Many neutral hypersaline environments at saturation point, harbour climax populations of halobacteria usually belonging to the genera Halobacterium, Haloarcula and Halorubrum [46].Representatives of other genera are much less common [30,51], although detailed characterisation at the species level is seldom carried out. In this paper we report the characterization of five halobacterial isolates from a sebkha near Ain Salah in Algeria, able to produce biosurfactants, whose production and partial characterization are described.…”
mentioning
confidence: 99%
“…Antibiotic sensitivity data can also be used as strain markers in the biotechnological scale and may help to exclude unwanted halophilic Archaebacterial strains in possibly mixed cultures. On the basis of the salinity and the chemical properties of the brine and salt samples examined, dominance of red halophilic Archaea was expected (Rodriguez-Valera 1988;Oren 1994aOren , 2002.…”
Section: Discussionmentioning
confidence: 98%
“…Generally such a colouration of the brine is only obtained when red halophilic Archaea are present in numbers exceeding 10 7 per ml, although some contribution of b-carotene-rich Dunaliella cells may also contribute to the colour (Oren 1994a(Oren , 2002.…”
Section: Discussionmentioning
confidence: 98%